Biscuit's Pet & Play Farm Animals : A TOUCH & FEEL BOOK - Capucilli, Alyssa Satin, 1957-; Berlin, Rose Mary; Schories, Pat (New York, NY : Harper Festival, 2018)
Join Biscuit, everyone's favorite little yellow puppy, as he meets baby farm animals in this touch-and-feel board book!
Interest age level: Newborn to 4
Keywords: Biscuit (Fictitious character) -- Juvenile fiction; Dog -- Juvenile fiction; Domestic animals -- Juvenile fiction; Board books